Meta-analysis and indirect treatment comparison of lipegfilgrastim with pegfilgrastim and filgrastim for the reduction of chemotherapy-induced neutropenia-related events. (September 2018) - Bond, T Christopher; Szabo, Erika; Gabriel, Susan; Klastersky, Jean; Tomey, Omar; Mueller, Udo; Schwartzberg, Lee; Tang, Boxiong
Background: Granulocyte colony-stimulating factors are effective at reducing the risk and duration of neutropenia. The current meta-analysis compared the neutropenia-related efficacy and safety of lipegfilgrastim to those of pegfilgrastim and filgrastim. Methods: Embase was searched for trials examining the efficacy/safety of lipegfilgrastim, pegfilgrastim, or filgrastim. Outcomes included febrile neutropenia, severe neutropenia, duration of severe neutropenia, time to recovery of absolute neutrophil count, and incidence of bone pain. Direct comparisons were made using random-effects models. No trials directly compared lipegfilgrastim and filgrastim. Indirect comparisons were made between lipegfilgrastim and filgrastim with pegfilgrastim as the common comparator. Results: This meta-analysis included a total of 5769 patients from 24 studies. Over all cycles, lipegfilgrastim showed a lower, nonsignificant risk of febrile neutropenia compared with pegfilgrastim. Lipegfilgrastim has a lower risk of febrile neutropenia versus filgrastim but was also not statistically significant. The risk ratio for severe neutropenia in cycle 1 was 0.80, a 20% reduction in favor of lipegfilgrastim. For cycles 2–4, the risk ratio was 0.53 (0.35, 0.79) for lipegfilgrastim versus pegfilgrastim. The risk of severe neutropenia in cycles 2–4 was also significantly lower for lipegfilgrastim (risk ratio 0.45, 0.27, 0.75, respectively). No significant differences were found for febrile neutropenia and severe neutropenia in cycle 1. However, in cycles 2–4, lipegfilgrastim was associated with significant and clinically meaningful reductions in risk of severe neutropenia versus either pegfilgrastim or filgrastim. Conclusions: Compared with pegfilgrastim or filgrastim, lipegfilgrastim has a statistically significantly lower absolute neutrophil count recovery time; however, differences in duration of severe neutropenia and bone pain were nonsignificant.